Spread bancário e enforcement contratual: hipótese de causalidade reversa e evidência empírica - Salama, Bruno Meyerhof (2016)
The consensus in the literature is that the low level of enforcement of contracts and guarantees is an important cause of Brazil’s high banking spreads. There may however be an endogeneity problem in the estimation of this causal effect due to reverse causality. This paper formulates this hypothesis, presents preliminary empirical evidence and draws normative implications. At the end, it presents useful lessons for economic analysis of law and of the Judiciary Power.